(untitled) (Al-Qamar, 2021)
This article discusses the approaches used by the non-Muslim writers to study the autobiography of Holy Prophet Muhammad (Peace Be Upon Him). It discusses in detail the artistic trends of the non-Muslim writers e.g., prejudiced work, narrow minded work, favourable work of the writers, dubious or false narrations, non-trustworthy narrations, self-made theories, destroying or hiding the true facts etc. The article takes into account different sources of autobiographies, articles, books etc. to compare to one another and conclude the artistic work of the non-Muslim writers.